TECHNOLOGICAL APPROACH TO PREPARING FUTURE TEACHERS TO THE ORGANIZATION OF LABOR STUDY OF YOUNG SCHOOLS - Balakireva, Victoria (Mountain School of Ukrainian Carpaty, 2018)
The article deals with the technological approach as a means of preparing future teachers for the organization of labor education for junior pupils. The concept of "approach", "technology", "pedagogical technology", "technological approach" is substantiated. The possibility of using a technological approach in preparing future teachers for organizing labor training for younger students in a modern institution of higher education has been explored. Technological approach combines the use of various technologies: modeling of educational information in the form of differentiated tasks of varying degrees of complexity; assimilation of educational material in the form of dialogues, which ensures subjective-semantic communication, reflection, self-actualization of personality; simulation of problem and game situations, the search for the exit of which ensures the implementation of personal functions in conditions of internal conflict, competition. The development of pedagogical technology in the world educational space can be divided into three stages, each of which is characterized by the advantage of one or the same trend. The main trend in the first phase was to improve the quality of teaching, which was seen as the only way that led to effective learning. Efforts were made to increase the effectiveness of teaching by raising the level of information education through the use of mass media. The second stage was characterized by a shift in emphasis on the learning process, which was due to the development of the concept of programmable learning, which required strict consideration of age and individual differences of students. Attention to the learning process has led to an awareness of the fact that it determines the teaching methodology and is a criterion for success in general. The third stage, modern, is characterized by the expansion of the sphere of pedagogical technology. If earlier its functions were reduced to the actual maintenance of the learning process, now pedagogical technology claims to play a leading role in planning, organizing the learning process, developing methods and training tools. Technological approach is complex, open systems of certain techniques and techniques conceptually united by priority educational goals, which are interconnected tasks and content, forms and methods of organization of the educational process, where each element of this system imposes an imprint on all other elements. Technological approach combines the use of various technologies: multimedia; mobile; web quest technology; simulation game; design Simulation of educational information in the form of differentiated tasks of varying degrees of complexity.